2022
DOI: 10.3390/land11081313
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Cadmium Accumulation in Maize (Zea mays L.) and Soil Influenced by Phosphoric Fertilizers in Two Different Textured Soils

Abstract: Non-nutritive metals, especially cadmium (Cd), are present in P fertilizers; the long-term application of these P fertilizers leads to Cd build-up in the soil. The current study aims to evaluate the impacts of P sources and rates on the growth of maize (Zea mays L.) and the bioavailability of Cd. Twelve treatments including rock phosphate 4 g kg−1 (RP1); 8 g kg−1 (RP2); 12 g kg−1 (RP3)); single super phosphate 333 mg kg−1 (SSP1); 444 mg kg−1 (SSP2); 555 mg kg−1 (SSP3); di-ammonium phosphate 130 mg kg−1 (DAP1);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Among the various P fertilizer types, DAP and DCP application had the most pronounced impact on enhancing biomass in all plant parts, while SSP and MAP had a lesser effect (Figure 1). P plays a crucial role in multiple metabolic processes and promotes the growth of plant biomass [31]. Liu et al [32] reported that the combination of biochar and a high concentration of phosphate fertilizer not only increased pasture biomass but also reduced Cd concentration, ensuring pasture safety standards.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various P fertilizer types, DAP and DCP application had the most pronounced impact on enhancing biomass in all plant parts, while SSP and MAP had a lesser effect (Figure 1). P plays a crucial role in multiple metabolic processes and promotes the growth of plant biomass [31]. Liu et al [32] reported that the combination of biochar and a high concentration of phosphate fertilizer not only increased pasture biomass but also reduced Cd concentration, ensuring pasture safety standards.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat, used mainly for further processing, ranks among essential agricultural commodities on the global market. However, its production suffers from the limited availability of phosphorus, which disappears due to resource depletion from the fertile ground (Majeed et al 2018;Suleman et al 2022). Wheat is also a vital nutrient whose lack leads to prolonged starvation of local consumers in many global regions (Yazbeck et al 2022).…”
mentioning
confidence: 99%